Psychological Vulnerability and Subjective Happiness: The Mediating Role of Hopelessness - Satici, Seydi Ahmet; Uysal, Recep (WILEY, 2017)
The current study examined the mediating role of hopelessness on the relationship between psychological vulnerability and subjective happiness. It was anticipated that hopelessness may act as a mediator in the relationship between psychological vulnerability and subjective happiness. Two hundred sixty-nine (150 women and 119 men) university students completed the Psychological Vulnerability Scale, the Subjective Happiness Scale and the Beck Hopelessness Scale. Data have been collected in the 2013-2014 academic year. The present study was designed as a cross-sectional study. Correlational results indicated that psychological vulnerability and hopelessness were significantly negatively associated with subjective happiness. Results using structural equation modelling showed that hopelessness fully mediated the relationship between psychological vulnerability and subjective happiness. Implications for future research and limitations of the present study are discussed. Copyright (c) 2016 John Wiley & Sons, Ltd.
Keywords: psychological vulnerability; subjective happiness; hopelessness; Turkish participants; DEPRESSIVE SYMPTOMS; SOCIAL COMPETENCE; HOPE; SCALE; SAMPLE; INDIVIDUALS; RELIABILITY; CONSTRUCT; MEN; Psychology; Psychiatry